Sulphur Concretes of Framework Structure. Issue 5 (March 2021) - Erofeev, V; Yausheva, L; Bulgakov, A
Abstract: From the standpoint of the multi structure theory, the principles of the formation of sulphur concrete composite materials are proved. The regularities of structure formation and the manufacturing technology of frame composites at the levels of micro- and macrostructure are determined. Theoretically and experimentally substantiated the optimal composition of composites for the manufacture of coatings and floors, resistant to exposure to chemical and biological aggressive environments. The influence of the nature and dispersion of the filler, its quantitative content on the structure formation, transparency and durability of sulphur composites is investigated. Active additives for sulphur concrete are proposed, which make it possible to increase their mechanical-and-physical properties, as well as durability under conditions of exposure to chemical aggressive environments and microorganisms. The preparation technology is developed and the mechanical-and-physical properties of the frame structure composites are determined.